PERLINDUNGAN HUKUM BAGI ANAK DIBAWAH UMUR YANG DIJADIKAN PEKERJA SEKS KOMERSIAL DI KOTA BATAM - Jack Taosen; Eko Nurisman (Universitas Muhammadiyah Ponorogo, 2022)
Children are a form of gift given by God to parents. A child is every individual who is under the age of 18 years and is not yet proficient in law. So in this case, of course, both parents are the most important figures in the process of growing and developing children. The changing times that are increasingly developing are certainly a form of lifestyle changes that can trigger the emergence of new social problems. The problems that have emerged lately are economic problems that make it difficult for everyone to meet the necessities of life, so that some parents have the heart to commit disgraceful actions by making their children as commercial sex workers, this is also felt by some people, especially Batam City. The purpose of this research is to find out the government's legal protection policy in protecting minors who are used as commercial sex workers, as well as what are the main factors or causes of minors being made commercial sex workers. In solving this problem the research method used is a juridical-empirical research method, namely by using a primary and secondary data approach. Based on the results of policy research conducted by the government in protecting minors in Batam City, it is regulated in Regional Regulation Number 5 of 2013 concerning Prevention and Handling of Victims of Trafficking in Persons. Where in this case the legal protection efforts carried out by the Batam City government consist of 3 stages of efforts in the form of pre-emptive efforts, preventive efforts, and repressive efforts. Then it refers to Article 88 of Law Number 35 of 2014 concerning Child Protection, Article 2 of Law Number 21 of 2007 concerning the Crime of Trafficking in Persons (PTPPO). Factors that influence children to become commercial sex workers include: Family, economy, environment and so on.